Outsourcing as a Mean of Service for Security Provision - D.I. Persanov (Безопасность информационных технологий, 2012)
The article highlights the implementation of outsourcing as a mean of service for security provision. Analysis is performed to describe the current issues affecting the management decision in favor of outsourcing. Investigation covers the processes of physical, information and economical security. The main recommendations to use outsourcing for security provision are described in the conclusion.